REPORT: WELFARE STATE MODEL – NORDIC EXPERIENCES AND PERSPECTIVES IN LITHUANIA - Bakutis, Romualdas (Baltic Journal of Political Science, 2015)
The aim of this article is to review the ideas presented by the Nordic scholars of the “Welfare State Model – Nordic Experiences and Perspectives in Lithuania” project and to discuss the applicability of these ideas to the Lithuanian context. During the program, held in Lithuania, in 2013–2014, Nordic scholars and their Lithuanian colleagues debated Nordic welfare model features such as active labour market policies, family policies, digital welfare innovations, the role of culture, and social trust. They also discussed contemporary challenges to Nordic success. The project intended to: promote the Nordic countries’ experiences of becoming welfare states, increase knowledge of the Nordic welfare model among Lithuanians, and initiate a debate on the potential for this model to function in Lithuania.